2017
DOI: 10.11648/j.ajche.20170504.13
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Consciousness Energy Healing Treatment on the Physicochemical and Thermal Properties of Magnesium Gluconate

Abstract: Magnesium gluconate is usually used as a dietary supplement for the prevention and treatment of hypomagnesemia as well as to maintain the overall quality of life. The present study was designed to evaluate the impact of The Trivedi Effect ® -Energy of Consciousness Healing Treatment on the physicochemical and thermal properties of magnesium gluconate using PXRD, PSA, DSC, and TGA/DTG analysis. Magnesium gluconate was divided into two parts -one part was control (without Biofield Energy Treatment), while anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…C/12 C or17 O/16 O) was significantly increased by 76.54% in the Biofield Energy Treated nanocurcumin compared to the control sample. Therefore, the13 C, 2 H, and 17 O contributions from C 21 H 21 O 6 + to m/z 370 in the Biofield Energy Treated sample was significantly increased compared to the control sample.…”
mentioning
confidence: 90%
“…C/12 C or17 O/16 O) was significantly increased by 76.54% in the Biofield Energy Treated nanocurcumin compared to the control sample. Therefore, the13 C, 2 H, and 17 O contributions from C 21 H 21 O 6 + to m/z 370 in the Biofield Energy Treated sample was significantly increased compared to the control sample.…”
mentioning
confidence: 90%
“…To improve the bioavailability of curcumin, numerous approaches have been undertaken. Numerously published literature indicated that the Trivedi Effect ® -Consciousness Energy Healing Treatment has the impact on the various properties of drug substances that would be helpful in the modification of physicochemical, spectral, and thermal properties of pharmaceutical/ nutraceutical compounds [14][15][16][17]. Biofield Energy is a unique paradimensional electromagnetic field exists in the human body, resulting in the continuous emission of energy from the body, which can freely flow between the human and environment [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the Trivedi Effect ® -Biofield Energy Treatment have been scientifically reported with remarkable and outstanding results in the field of biotechnology [22,23], microbiology [24,25], pharmaceutical/nutraceutical sciences [14][15][16], medical science [26,27], materials science [28,29], agriculture [30,31], etc. The Trivedi Effect ® also found to have a remarkable effect of altering the isotopic abundance ratios of various compounds may be through the possible mediation of neutrinos [17,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Other than this numerous sources for Mg are nutraceutical and pharmaceutical preparations, i.e., Mg gluconate, citrate, chloride, aspartate, or lactate [4]. Deficiency of plasma Mg (called hypomagnesaemia) is a very general problem in most of electronic components [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Mg can be explosive hazards; it is highly reactive with water, flammable at the temperature of approximately 3100 °C and the auto-ignition at the temperature of 473 °C [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Mg salt also has numerous applications in nutraceutical and pharmaceutical industry for the inflammatory diseases, immunological disorders, diabetes mellitus, allergies, cancer, septic shock, asthma, gestational hypertension, oxidative stress, hearing loss, etc. Salt of Mg also used as a potent antioxidant agent, laxative, antacid, neuroprotective, oral tocolytic agent, and skin-tightening antiaging cosmetic composition [2,[11][12][13][14][15][16]. In heavy industry Mg used for the structural metal, aluminium alloys, die-casting, aircraft, automobiles, reagents in the organic synthesis, manufacturing of mobile phones, laptop and tablet computers, cameras, and other…”
mentioning
confidence: 99%